Prevalence of and factors associated with dental anxiety among medical and dental students of the Northern State Medical University, Arkhangelsk, North-West Russia - Drachev, Sergei; Brenn, Tormod; Trovik, Tordis A (International Journal of Circumpolar Health, 2018)
The following article, Drachev, S., Brenn, T. & Trovik, T.A. (2018). Prevalence of and factors associated with dental anxiety among medical and dental students of the Northern State Medical University, Arkhangelsk, North-West Russia. International Journal of Circumpolar Health , 77(1), can be accessed at https://doi.org/10.1080/22423982.2018.1454786 . The objective was to assess the prevalence of and factors associated with dental anxiety (DA) in medical and dental students in North-West Russia. This cross-sectional study included 422 medical and 285 dental undergraduate Russian students aged 18–25 years from the Northern State Medical University in Arkhangelsk. Corah’s Dental Anxiety Scale (DAS) was applied to measure DA. Information on socio-demographic and socioeconomic factors, oral health behaviour and general and oral health was obtained from a structured, self-administered questionnaire. A clinical examination was performed to assess caries experience, Simplified Oral Hygiene Index, and Gingival Index. DAS score ≥13 was found in 13.7% and 2.2% of medical and dental students, respectively. Female sex (incidence rate ratio [IRR] = 1.11, p = 0.013), lower education of mother (IRR = 1.13, p = 0.001), and poor self-assessed oral health (IRR = 1.15, p < 0.001) were associated with DA in medical students. Corresponding factors in dental students were female sex (IRR = 1.16, p = 0.001), irregular dental visits (IRR = 1.19, p = 0.001), infrequent tooth-brushing (IRR = 1.17, p = 0.007), pain in mouth (IRR = 1.09, p = 0.031) and number of missing teeth (IRR = 1.13, p = 0.007). The prevalence of high DA was lower in dental students than in medical students. DA was associated with sex, mother’s education, poor oral health behaviour and self-assessed and clinically assessed oral health.